2017
DOI: 10.1002/pssb.201700543
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Poisson's Ratios in Planar Isotropic Crystals of Binary Hard Discs at High Pressures

Abstract: Several isotropic two‐dimensional crystalline structures are described that exhibit maximum values of the Poisson's ratio at very high pressures. The considered crystals are formed by hard discs of two different diameters which are very close to each other. The investigations of the models are based on Monte Carlo simulations in the isobaric–isothermal ensemble with variable shape of the periodic box.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Finally, in the paper Maximum Poisson's ratios in planar isotropic crystals of binary hard discs at high pressures by Tretiakov, Bilski, and Wojciechowski , several isotropic two‐dimensional crystalline model structures, formed by hard discs of two slightly different diameters, are studied by Monte Carlo simulations in the isobaric–isothermal ensemble with variable shape of the periodic box. Some of the structures are shown to exhibit maximum values of Poisson's ratio in the limit of very high pressures, i.e.…”
mentioning
confidence: 99%
“…Finally, in the paper Maximum Poisson's ratios in planar isotropic crystals of binary hard discs at high pressures by Tretiakov, Bilski, and Wojciechowski , several isotropic two‐dimensional crystalline model structures, formed by hard discs of two slightly different diameters, are studied by Monte Carlo simulations in the isobaric–isothermal ensemble with variable shape of the periodic box. Some of the structures are shown to exhibit maximum values of Poisson's ratio in the limit of very high pressures, i.e.…”
mentioning
confidence: 99%
“…This, together with the behaviour under shear loading, merits further investigation. It should also be appreciated that the work by Tretiakov et al has also studied what can be considered as very similar structures to what was studied but using a rather different intermolecular potential. This work by Tretiakov et al had suggested completely different properties, thus highlighting the critical role of the intermolecular potential on the macroscopic properties of the systems studied.…”
Section: Resultsmentioning
confidence: 98%
“…To investigate further, the worst-case scenario when n ¼ 1, Figure 6 compares the Poisson's ratio and Young's modulus obtained numerically with the analytical models represented by the simple model derived in this work (Equations (29) and (30)), the advanced model (Equations (59) and (60)), and the standard results (Equations (31) and (32)). Here, the typical configuration consisting of l ¼ 2 h and t E ¼ t I , corresponding to α ¼ 2 and χ ¼ 1, were used.…”
Section: Resultsmentioning
confidence: 99%
“…The equations so derived contain correction factors that account for the effective bending lengths as well as axial and shear deformations. If these corrections are ignored, the resultant equations become once again Equation (29) and (30). Before proceeding, it is important to note that the advanced model does not consider the deformation induced in the intersecting parts of the ligaments.…”
Section: The Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation